2022
DOI: 10.1016/j.ultsonch.2021.105888
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of sonochemical and sonophysical effects in a 20 kHz probe-type sonoreactor: Enhancing sonophysical effects in heterogeneous systems with milli-sized particles

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Studies investigating the applied frequency and input power, which are the most basic experimental conditions, have consistently reported that enhanced sonochemical effects can be obtained by applying a frequency of several hundred kilohertz and an appropriate input power [1] , [2] . Furthermore, to enhance sonochemical oxidation, the combination with other advanced oxidation processes (AOPs) and the addition of oxidizing agents/dissolved gases/particulate matter has also been examined [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] . Recent studies have actively investigated geometric effects, such as changes in the size/shape of the reactor, as well as the transducer location and liquid level in the ultrasonic reactor [11] , [12] , [13] , [14] , [15] , [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating the applied frequency and input power, which are the most basic experimental conditions, have consistently reported that enhanced sonochemical effects can be obtained by applying a frequency of several hundred kilohertz and an appropriate input power [1] , [2] . Furthermore, to enhance sonochemical oxidation, the combination with other advanced oxidation processes (AOPs) and the addition of oxidizing agents/dissolved gases/particulate matter has also been examined [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] . Recent studies have actively investigated geometric effects, such as changes in the size/shape of the reactor, as well as the transducer location and liquid level in the ultrasonic reactor [11] , [12] , [13] , [14] , [15] , [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated sonochemical activity in solid particle suspensions [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] and in bubbly liquids [23] , [24] , [25] , [26] and are mostly concerned with how the quality and quantity of these solid/gas phases influence bubble characteristics and sonoreactions. Surface roughness, size, and shape are the most-studied indicators of particle quality.…”
Section: Introductionmentioning
confidence: 99%